Functional profiling of synthetic camel milk-derived peptides with implication in glucose transport and diabetes. - Irfa Anwar; Farheen Badrealam Khan; Bincy Baby; Priya Antony; Priti Mudgil; Chee-Yuen Gan; Sajid Maqsood; Ranjit Vijayan; Khalid Muhammad; Mohammed Akli Ayoub (PLoS ONE)
We previously identified protein hydrolysates from camel milk (CM) targeting dipeptidyl peptidase IV (DPP-IV) and insulin receptor (IR) activity. In this study, we synthesized nine peptides (P1 to P9) derived from such CM hydrolysates and profiled their potential bioactivity in vitro and in silico. This aims to validate and determine if such synthetic and pure CM-derived peptides are bioactive on IR function and glucose uptake using pharmacological and functional approaches in human embryonic kidney (HEK293) and human hepato-carcinoma (HepG2) cells. Our bioluminescence resonance energy transfer (BRET) results showed a partial activity of most peptides on IR activity in HEK293 cells ranging from 13 ± 1% to 65 ± 4%, and their potency varies from 3.13 ± 1.72 μg/ml to 12.30 ± 5.66 μg/ml. Combining the saturating dose (0.1 mg/ml) of peptides with insulin (1 μM) revealed three different profiles: non-efficient, potentiating, and antagonistic peptides. The potentiating effect of the peptides was from 104 ± 18% to 147 ± 11%, with one peptide (P2) reducing insulin's response to 52 ± 8%. Moreover, the peptides slightly promoted IR and AKT phosphorylation and glucose uptake in HepG2 cells with an efficacy of 56 ± 9% to 150 ± 18% on glucose transport. Our molecular docking study on the insulin-bound IR complex identified a potential allosteric binding site for specific bioactive peptides. Overall, our data confirmed the bioactivity of the synthetic CM-derived peptides on IR, AKT, and glucose uptake, consistent with the previous study on CM hydrolysates. The synthesis of the peptides and their validation provide further molecular insights into the antidiabetic action of CM. The study should pave the way for further in vitro and in vivo characterization of the peptides and developing potent and safe antidiabetic drugs based on the different CM-derived peptides described here.